ANALISIS KARAKTERISTIK DAN KEBUTUHAN PARKIR DI BANDARA INTERNASIONAL I GUSTI NGURAH RAI-BALI - Putu Adhiya Garini Putri, Dewa Ayu; Suthanaya, Putu Alit; Agus Ariawan, I Made (JURNAL SPEKTRAN; Vol 5 No 2 (2017): Vol. 5, No. 2, Juli 2017, 2017)
I Gusti Ngurah Rai International Airport has high numbers of car parking users, however land availaibility is limited to accomodate entire vehicle. This research was conducted to study about  the characteristic of parking and future parking needs. The aim of this study was to analyze the characteristics of parking on weekdays, weekends, and public holiday at Ngurah Rai Internasional Airport, also future parking needs. The method used to obtain data throught direct survey and recording primary data from PT. Angkasa Pura I (Persero). The analysis was performed by comparing characteristics on weekdays, weekends and holiday on motorcycle (2 wheelers), car (4 wheelers), and bus (6 wheelers). The highest parking indexs of motorcycles in on working days is 4.75. The highest parking indexs of car is on the weekend day is equal to 1.84. The highest perking indeks of bus is on the public holiday is equal to 7.54. I Gusti Ngurah Rai Airport still requires parking lots to meet parking needs. Based on characteristics parking, for motorcycle there was deficiency of 3.092 SRP, total parking lots requirement for car is 1.897 SRP and for bus is 42 SRP.     Keywords: parking, parking characteristic, parking needs .